A novel combination of non-self modelling and real-time visual feedback to improve rowing performance - Anderson, R.; Darling, J. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This study assesses the use of a method of concurrent video feedback combined with non-self modelling to assist learning and performance in rowing. A video image, containing a live video feed, is presented to the participant combined with a pre-recorded video sequence of an elite rower at various stroke rates. Sixteen volunteers participated in the study (20.8+1.7 years); eight were allocated to the experimental group (E) and eight to the control group (C). Data pertaining to rowing skill (stroke length (SL) and stroke rate (SR)) and rowing performance (overall distance (D) and average power (AP)) were obtained during a pre- and post-test separated by a seven-week intervention period. The results illustrate significant changes in all four parameters for the experimental group; D - P=0.013, AP - P=0.011, SL - P=0.001, & SR - P=0.042. The control group demonstrated significant changes in skill (SL - P=0.003; SR - P=0.005) and no significant differences in performance (D - P=0.21; AP - P=0.093). The results indicate that concurrent real-time video feedback had a positive effect on both skill acquisition and performance of the rowing motor skill for beginner rowers.